Petechiae in the newborn: A sign to consider - Gaia, Maria João; Brandão Silva, Joana; Capela, Mariana; Pinto, Rui (BIRTH AND GROWTH MEDICAL JOURNAL, 2023)
Neonatal alloimmune thrombocytopenia (NAIT) occurs when the mother develops antiplatelet antibodies against fetal platelets and is confirmed by the presence of maternal antihuman platelet antibodies. A full-term newborn from a first pregnancy without complications was routinely examined on the first day of life. The newborn appeared well and had multiple petechiae on the axillary, inguinal, and popliteal folds and on the lower abdomen, with no other findings. Blood work revealed thrombocytopenia of 28,000/ul with a normal remaining hemogram and negative C-reactive protein. Because of the suspicion of NAIT, an intravenous dose of immunoglobulin was administered with a subsequent increase in platelet count. The diagnosis was confirmed on day 5 with the detection of maternal antiplatelet anti-HPA-1a alloantibodies. A thorough physical examination of the newborn is essential, as some serious conditions may present with subtle changes. NAIT should be considered in the differential diagnosis of isolated petechiae of the newborn.